Fair Value Accounting and Audit Fees: The Moderating Effect of The Global Financial Crisis in Jordan - Esraa Esam Alharasis; Maria Prokofieva; Colin Clark (Asian Academy of Management Journal of Accounting and Finance, 2022)
This article introduces new empirical evidence exploring the relationship between the introduction of Fair Value Disclosure (FVD) and audit fees, and the moderating effect of the Global Financial Crisis (GFC) on this relationship. This study is primarily motivated by the limited and inconclusive research on the monitoring costs resulting from FVD. The Ordinary Least Squares (OLS) method using a sample of 222 Jordanian firms during 2005–2018 is applied. The analysis finds that a greater level of FVD is the major cause of high audit fees. Results are more pronounced for firms with larger proportions of subjective FVDs (Level 3 assets). A significant negative (positive) impact of the pre- crisis (post-crisis) period on the association between the proportion of fair-valued assets and audit fees is confirmed. The regression results confirm the negative effect of pre-crisis period on moderating the association between the all-fair value input levels (Levels 1, 2 and 3 assets) and audit fees. The post-crisis period has a significant positive effect only in relation to Level 1 assets. Findings of this study provide policymakers and standards setters with updated evidence originating from a non-Western setting about the post-implementation costs of FVD.